Role of tumour location and surgical extent on prognosis in T2 gallbladder cancer: an international multicentre study. Issue 10 (26th May 2020) - Kwon, W; Kim, H; Han, Y; Hwang, Y J; Kim, S G; Kwon, H J; Vinuela, E; Járufe, N; Roa, J C; Han, I W; Heo, J S; Choi, S-H; et al.
Abstract: Background: In gallbladder cancer, stage T2 is subdivided by tumour location into lesions on the peritoneal side (T2a) or hepatic side (T2b). For tumours on the peritoneal side (T2a), it has been suggested that liver resection may be omitted without compromising the prognosis. However, data to validate this argument are lacking. This study aimed to investigate the prognostic value of tumour location in T2 gallbladder cancer, and to clarify the adequate extent of surgical resection. Methods: Clinical data from patients who underwent surgery for gallbladder cancer were collected from 14 hospitals in Korea, Japan, Chile and the USA. Survival and risk factor analyses were conducted. Results: Data from 937 patients were available for evaluation. The overall 5-year disease-free survival rate was 70·6 per cent, 74·5 per cent for those with T2a and 65·5 per cent among those with T2b tumours ( P =  0·028). Regarding liver resection, extended cholecystectomy was associated with a better 5-year disease-free survival rate than simple cholecystectomy (73·0 versus 61·5 per cent; P =  0·012). The 5-year disease-free survival rate was marginally better for extended than simple cholecystectomy in both T2a (76·5 versus 66·1 per cent; P =  0·094) and T2b (68·2 versus 56·2 per cent; P =  0·084) disease. Five-year disease-free survival rates were similar for extended cholecystectomies including liver wedge resection versus segment IVb/V segmentectomy (74·1 versus 71·5 per cent; P =  0·720). In multivariable analysis, independent risk factors for recurrence were presence of symptoms (hazard ratio (HR) 1·52; P =  0·002), R1 resection (HR 1·96; P =  0·004) and N1/N2 status (N1: HR 3·40, P < 0·001; N2: HR 9·56, P < 0·001). Among recurrences, 70·8 per cent were metastatic. Conclusion: Tumour location was not an independent prognostic factor in T2 gallbladder cancer. Extended cholecystectomy was marginally superior to simple cholecystectomy. A radical operation should include liver resection and adequate node dissection. Graphical Abstract: This multinational multicentre cohort study was undertaken to investigate the prognostic value of tumour location in T2 gallbladder cancer and to clarify the adequate extent of surgical resection. Although tumour location influenced prognosis, it was not an independent prognostic factor in T2 gallbladder cancer. T2 gallbladder cancer requires extended cholecystectomy including hepatic resection and lymph node dissection, regardless of the location. challenges current TNM system